Environmental Assessment of Alkali-Catalysed Biodiesel Process Using War Algorithm - Siti Faiznur, Daud (2013)
A continuous homogenous chemical process flow sheet for biodiesel production from waste cooking oil under alkaline conditioning was developed. The process simulation was conducted by using Aspen Plus software simulator since it can optimize the simulation process. Details on the operating conditions and equipment designs for the process were obtained from the previous research. By defining suitable indicators from the result obtained, the potential environmental impact (PEI) of the process towards the environment can be conducted. Hence to determine the PEI value, WAR Algorithm is then introduced. It is used to evaluate the environmental friendliness of a process and was carried out by using the developed Microsoft Excel spread sheet. There are four PEI indexes involved (TRO, TOP, TRG and TGP) as the comparative manner. To evaluate in PEI indexes, eight PEI categories are used (HTPI, HTPE, ATP, TTP, GWP, PCOP and AP). The result of PEI value obtained was compared with the heterogeneous chemical process. As conclusion, heterogeneous catalysed is desirable chemical process since it was produced lower PEI value and had lower chemical impact towards the environment compared to homogenous chemical process.